2019
DOI: 10.1051/0004-6361/201834573
|View full text |Cite
|
Sign up to set email alerts
|

Gaia GraL: Gaia DR2 gravitational lens systems

Abstract: We report the spectroscopic confirmation and modeling of the quadruply imaged quasar GRAL 113100-441959, the first gravitational lens (GL) to be discovered from a machine learning technique that only relies on the relative positions and fluxes of the observed images without considering colour informations. Follow-up spectra obtained with Keck/LRIS reveal the lensing nature of this quadruply imaged quasar with redshift z s = 1.090 ± 0.002, but show no evidence of the central lens galaxy. Using the image positio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…GraL J113100.0−442000 -This system was modeled in GraL IV (Wertz et al 2019). The models presented here agree with the previous ones.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…GraL J113100.0−442000 -This system was modeled in GraL IV (Wertz et al 2019). The models presented here agree with the previous ones.…”
Section: Resultssupporting
confidence: 87%
“…GraL J113100.0−442000 -This is the quadruply-imaged quasar presented as a candidate in Krone-Martins et al ( 2018) and Delchambre et al (2019), and then spectroscopically confirmed and modelled in Wertz et al (2019). The latter is a detailed paper dedicated to this single source.…”
Section: Confirmed Quad Lensesmentioning
confidence: 74%
See 1 more Smart Citation
“…The system 11310013-1149559935 has been observed to have a timing variation indicative of gravitational lensing [10]. Our data then agrees well with this additional evidence, as we have demonstrated this system has geometric properties consistent with lensing.…”
Section: Resultssupporting
confidence: 86%
“…According to the NASA ADS, the majority of the new publications are related to the fields of Galactic halo and disk studies (see below), but also to solar system studies (Cellino et al, 2007;Gaia Collaboration et al, 2018d), exoplanet and host star characterization (Kervella et al, 2019), characterization of variable or binary objects (Ziegler et al, 2018) and of objects with astroseismological data (Berger et al, 2018). Work was done also in the field of extragalactic studies, for example on Quasars variability (Hwang et al, 2019) or gravitational lensing (Wertz et al, 2019). Gaia DR2 data have even been used to search for a plausible home star for the interstellar object 'Oumuamua (Bailer-Jones et al, 2018), which recently was discovered transiting in the solar system 12 .…”
Section: The Second Gaia Data Releasementioning
confidence: 99%